Ketersediaan Fosfor pada Tanah Andisol untuk Jagung (Zea maysL.) oleh Inokulum Bakteri Pelarut Fosfat - Tamad, ,; Ma’as, Azwar; Radjagukguk, Bostang; Hanudin, Eko; Widada, Jaka (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2013)
Andisols has relatively low phosphorus availability due to its adsorption by allophane. Phosphate solubilizing bacteria (PSB) increases the availability of P via release of adsorpted-P. The aims of this research were to determine: 1) anorganicP solubilization, 2) organic-P mineralization, 3) blocking of Andisols adsorption site, and 4) effective PSB inoculant. The research was arranged in completely randomized design, with PSB inoculant as treatment. Variables observed were solubleP, mineralize-P, adsorpted-P, pH, total acidity, PSB population, phosphatase and phythase activity, relative surface charge, and maize’s growth component. The result showed that PSB inoculation increased soluble-P from 30 to between 150 and 195 ppm P, increased mineralize-P from 23.7 to between 63.6 and 91.7 ppm P, and decreased P-adsorption from 95 to between 36 and 13%. PSB inoculation decreased the Andisols pH, increased the total acidity, PSB population, the phosphatase and phytase activity, and PSB had relatively high of relative surface charge (69%). The PSB inoculation increased maize P absorption in the range of 70 and 75 mg P plant-1, and increased relative agronomic effectiveness (RAE )between 145 and 150%. Liquid and solid PSB inoculant had no different effect in increasing maize growth. Keywords: Andisol, P release, phosphate solubilizing bacteria, phosphatase, phytase